Inhibitors of interleukin-1 receptor-associated kinase 4 (IRAK4): a patent review (2012-2015). (2nd August 2016) - Seganish, W. Michael
ABSTRACT: Introduction : IRAK4 is located proximal to TLR/IL-1 receptors, and in preclinical studies, inhibits downstream signaling from these receptors. The development of novel small molecule inhibitors of this kinase has the potential to lead to new therapeutics to treat diseases such as rheumatoid arthritis, lupus, and lymphomas. Areas covered : The aim of this review is to summarize the recent patent literature (2012–2015) surrounding small molecule inhibitors of IRAK4. Specific examples of the chemical matter from each patent will be discussed, including any data that are presented for the examples highlighted. Expert opinion : There are currently many examples of highly potent and kinase selective IRAK4 inhibitors and some have been tested in various in vivo disease models, demonstrating robust pre-clinical efficacy. Several compounds appear to have the 'drug-like' properties to advance to the clinic, with Pfizer having already initiated several phase I studies.